PENGEMBANGAN MEDIA KALKULUS MENGGUNAKAN JAVASCRIPT GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PENALARAN TERHADAP CALON GURU PADA PANDEMI COVID 19 - Martin Bernard; Chandra Novtiar (IKIP Siliwangi, 2022)
Calculus is one of the basic subjects that must be mastered by every student of the mathematics education study program, if students cannot understand other mathematics-related courses, students will experience difficulties and will hinder their professionals from becoming good teachers. Because, a teacher must be able to convey information that is important for mathematics to be applied to daily life to students, this encourages students to be motivated to develop mathematics in the future related to technology. In current developments, teachers are trying to make mathematics learning strategies by using teaching aids to improve students 'reasoning abilities, so that students can provide based on students' experiences when doing it, but the biggest obstacle by teachers is the cost that is too large and the time is too long. And as a consideration, making ICT-based media is more effective in overcoming these two factors by developing Javascript geometry.